Precision Of Dermoscopy In Melasma Over Wood’s Lamp Examination (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION– Melasma is a hyper pigmentary disorder resulting in areas of  pigmentation with irregular outline depending on the level of melanin deposition in skin. Skin  pigmentation can be attributed to various causes different for circumscribed and diffuse  hyperpigmentation. Clinical diagnosis though easy is better supported by tools such as woods  lamp and dermoscope thereby helping in making the diagnosis more accurate and sometimes  helping in monitoring the response after treatment. Conventionally used Wood’s lamp  classified melasma into epidermal, dermal and mixed types. These types are better categorised  by dermoscopy which is a new non-invasive office tool, coming with extra benefits. This study  aims to demonstrate precision of dermoscopy over Wood’s lamp and encourages its use. MATERIAL AND METHODS– A cross sectional study of 100 patients diagnosed clinically  as melasma was conducted over a period of seven months. Each patient was assessed by  Wood’s lamp and then with dermoscope. Photographs were taken and clinically noted  epidermal, dermal and mixed melasma types were confirmed according to the tool used.  Results were compared and analysed. RESULTS– Out of 100 patients, Wood’s lamp classified 62, 30, 8 patients into epidermal,  dermal and mixed melasma respectively while dermoscopy classified 43, 28 and 29 into the  same. Comparison was done between the results of Wood’s lamp and dermoscopy and the  degree of agreement was found to be substantial. (k= 0.6646, p
Keywords: Melasma; Dermoscopy; Wood’s lamp; Pigment pattern